Editorial - Quadros, Laura Cristina de Toledo; Prestrelo, Eleonôra Torres; Cavanellas, Luciana Bicalho; Soares, Luciana Loyola Madeira (Estudos e Pesquisas em Psicologia, 2020)
Laura Cristina de Toledo Quadros, Eleonôra Torres Prestrelo, Luciana Bicalho Cavanellas, Luciana Loyola Madeira Soares